Expeditions in the long nineteenth century discovering, surveying, and ordering - Happel, Jörn 1978-; Hussinger, Melanie; Raupach, Hajo (Routledge, Taylor & Francis Group, 2024)
"This book examines the processes of scientific, cultural, political, technical and violent appropriation during the 19th century. The 19th century was the century of world travel. The earth was explored, surveyed, described, illustrated, and categorized. Travelogues became world bestsellers. Modern technology accompanied the travelers and adventurers: clocks, a postal and telegraph system, surveying equipment, and cameras. The world grew together faster and faster. Previously unknown places became better known: the highest peaks, the coldest spots, the hottest deserts, and the most remote cities. Knowledge about the white spots of the earth was systematically collected. Those who made a name for themselves in the 19th century are still read today. Alexander von Humboldt or Charles Darwin made the epoch a scientific heyday. Ida Pfeiffer or Isabelle Bird (Bishop) traveled to distant continents and took their readers at home on insightful journeys. Hermann Vámbéry or Sir Richard Burton got to know the most remote languages and regions. There are countless travel reports about a fascinating century, which, with surveying and exploration, also brought colonial conquest and exploitation into the world. In ten individual studies, the authors explore travelers from all over the world and analyze their successes. The unifying element of all the studies is the experience of distance and its communication by means of travelogues to the armchair travelers who have stayed at home. This volume will be of value to students and scholars both interested in modern history, social and cultural history, and the history of science and technology."
Keywords: Geschichte 1789-1918; Expedition; Entdeckung; Wissensorganisation; Wissensproduktion; Forschungsreise; Aufsatzsammlung